Memory Impairment and Hippocampal Volume after Carbon Monoxide Poisoning. (7th August 2020) - Tamura, Takehiro; Sugihara, Genichi; Takahashi, Hidehiko
Abstract: Objective: We report longitudinal changes in neuroimaging and neuropsychological measurements in a case of carbon monoxide (CO) poisoning showing reversible changes in hippocampal volume, which was closely linked to the degree of memory impairment. Methods: The current study presents a female in her early 20s, with a high school level of education. She became aware of headaches and drowsiness while working in a restaurant that operated charcoal braziers, and she was urgently transported to our hospital. Her high blood carboxyhemoglobin concentration led to a diagnosis of CO poisoning, but no obvious abnormalities were found by brain magnetic resonance imaging (MRI) and physical examinations. She underwent a series of hyperbaric oxygen therapies. One year after CO poisoning, she consulted a psychiatrist due to her own awareness of gradually worsening memory function. She was assessed by brain MRI and standard neuropsychological tests every 6 months for 1 year. Results: Her neuropsychological profile showed the impairment of memory function according to a low score of Delayed Recall Index of Wechsler Memory Scale-Revised. At 320 days after CO poisoning, her hippocampal volume had decreased by 3%. Her memory function was found to have improved at 530 days after CO poisoning. Of note, during this period, her hippocampal volume had increased by approximately 7%. Conclusions: This report suggests that a clinician should conduct careful neuropsychological examinations to avoid overlooking mild sequelae of CO poisoning, even if a general assessment of brain MRI is normal.